Answer this ...........
# No spamming
Attachments:
![](https://hi-static.z-dn.net/files/d43/8fe4cc6def3093d99c273b6af0722ce1.jpg)
Steph0303:
eh ab diya iss question kho??
Answers
Answered by
12
HELLO BEHNA
REFER TO THE ATTACHMENT
HOPE IT HELPS !!! ☺✌
REFER TO THE ATTACHMENT
HOPE IT HELPS !!! ☺✌
Attachments:
![](https://hi-static.z-dn.net/files/dc8/34dc3344939308b82230967f23eca5a6.jpg)
Answered by
14
♧♧HERE IS YOUR ANSWER♧♧
Given :
sec²θ (1 + sinθ)(1 - sinθ) = k
or, sec²θ (1 - sin²θ) = k
or, sec²θ × cos²θ = k
or, 1 = k
or, k = 1
So, the value of k is 1.
Remember :
(a + b)(a - b) = a² - b²
1 - sin²θ = cos²θ,
by the relation (sin²θ + cos²θ = 1)
cosθ × secθ = 1
♧♧HOPE IT HELPS YOU♧♧
Given :
sec²θ (1 + sinθ)(1 - sinθ) = k
or, sec²θ (1 - sin²θ) = k
or, sec²θ × cos²θ = k
or, 1 = k
or, k = 1
So, the value of k is 1.
Remember :
(a + b)(a - b) = a² - b²
1 - sin²θ = cos²θ,
by the relation (sin²θ + cos²θ = 1)
cosθ × secθ = 1
♧♧HOPE IT HELPS YOU♧♧
Similar questions
Environmental Sciences,
8 months ago
Computer Science,
8 months ago
Math,
1 year ago
English,
1 year ago
Hindi,
1 year ago
English,
1 year ago
English,
1 year ago